Building from the bottom : infrastructure and poverty alleviation - Kochhar, Sameer; Ramachandran, M.; Debroy, Bibek; Academic Foundation (New Delhi, India); Skoch Consultancy Services; Skoch Development Foundation (New Delhi : Academic Foundation in association with Skoch Consultancy Services / Skoch Development Foundation, 2010)
Contributed articles in Indian context.
I.- Policy;--- II- Infrastructure; --- III- Governance and service delivery; ---IV- Poverty alleviation; --- Case studies.
Keywords: City planning -- India; City planning -- India -- Case studies; Urban renewal -- India -- Citizen participation; Urban poor -- Government policy -- India; Infrastructure (Economics) -- India; Desarrollo urbano -- India